Profinet Industrial Internet of Things Gateway for the Smart Factory - Johansson, Henrik (My University, 2017)
The Internet of Things revolution in industrial production environments imposes new requirements on devices, hardware and software in the production systems. In previous systems, each vendor could have their own proprietary protocols and platforms but as more and more devices and sensors are connected together, increased collaboration and standardization is necessary. This thesis aims to aid in building the bridge connecting an industrial system and the outside world, but also on solving an existing problem in industrial networks regarding the set up for new devices. The thesis also aims to give a compilation of protocols and platforms that can be used in industrial applications. A practical solution to bridging the networks and solving the problem is done by implementing an industrial network stack (Profinet) in a gateway device. The resulting prototype gateway can communicate with conventional network traffic as well as the industrial network protocol Profinet, with both master and slave functionality.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science